The effect of music therapy on physiological parameters of patients with traumatic brain injury: A triple-blind randomized controlled clinical trial. (August 2020) - Froutan, Razieh; Eghbali, Mohammad; Hoseini, Seyyed Hamid; Mazloom, Seyed Reza; Yekaninejad, Mir Saeed; Boostani, Reza
Abstract: Objective: This study aims to investigate the effect of music therapy integrated with family recollection on physiological parameters of patients with traumatic brain injury who are admitted to Intensive Care Units. Methods: Sixty patients were selected through convenience sampling and were then randomly assigned to the intervention group and control group. In the intervention group and for 6 consecutive days, the patients received a combination of music and auditory stimulation twice a day for 15 minutes. The patients' physiological parameters were measured before the intervention, and then 10 minutes and finally 30 minutes after the intervention. The data were analyzed using multilevel modeling method through MLwiN version 2.27. Results: The results showed that there was no significant difference between the two groups in terms of demographic factors and the duration of coma. However, the results of the two-level multiple linear models which were performed for 6 consecutive days indicated a significant decrease in systolic blood pressure, diastolic blood pressure, respiratory rate and heart rate for the patients in the intervention group as compared to the patients in the control group (P < 0.0001). Nevertheless, no significant difference was observed in temperature and oxygen saturation (P > 0.05). Conclusion: Integration of music therapy with family recollection can moderate physiological parameters. Therefore, it is recommended to use this cost-effective treatment along with the routine treatments, especially for patients with traumatic brain injury. Highlights: Traumatic brain injury (TBI) is known as a silent epidemic and leading cause of death and disability. . Hospitalization in the ICU is stressful for TBI patient and can lead to an increase in their physiological Parameter. Auditory stimulation with a familiar voice is one of the non-pharmacological interventions for stress control. The result of this study showed that familiar auditory stimulation can control and reduce SBP, DBP, HR, and respiration. . Familiar auditory stimulation did not have a significant impact on temperature and O2 saturation.